2022
DOI: 10.1039/d2sc03565k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ion mobility on the redox and catalytic properties of Cu ions in zeolites

Abstract: This contribution aims at analysing the current understanding about the influence of Al distribution, zeolite topology, ligands/reagents and oxidation state on ions mobility in Cu-zeolites, and its relevance toward reactivity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…The NH 3 –SCR–NO x reaction is currently employed for the removal of nitrogen oxides (NOx) from exhaust gases in diesel vehicles and stationary plants through a redox catalytic cycle in which Cu + is oxidized to Cu 2+ by O 2 , NO 2 , or NO + O 2 and then reduced to Cu + by the reaction of NH 3 and NO forming harmless N 2 + H 2 O (Scheme ). This understanding of the reaction mechanism has enabled the development of optimized catalysts by tuning the framework topology, composition, and copper speciation. In the as-prepared catalysts, Cu + and Cu 2+ cations are directly coordinated to the zeolite framework forming heterogeneous active sites, while under reaction conditions NH 3 solvates the Cu + cations forming mobile [Cu­(NH 3 ) 2 ] + complexes that act as dynamic active sites, resembling homogeneous catalysts but within the confinement of the zeolite pores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NH 3 –SCR–NO x reaction is currently employed for the removal of nitrogen oxides (NOx) from exhaust gases in diesel vehicles and stationary plants through a redox catalytic cycle in which Cu + is oxidized to Cu 2+ by O 2 , NO 2 , or NO + O 2 and then reduced to Cu + by the reaction of NH 3 and NO forming harmless N 2 + H 2 O (Scheme ). This understanding of the reaction mechanism has enabled the development of optimized catalysts by tuning the framework topology, composition, and copper speciation. In the as-prepared catalysts, Cu + and Cu 2+ cations are directly coordinated to the zeolite framework forming heterogeneous active sites, while under reaction conditions NH 3 solvates the Cu + cations forming mobile [Cu­(NH 3 ) 2 ] + complexes that act as dynamic active sites, resembling homogeneous catalysts but within the confinement of the zeolite pores.…”
Section: Introductionmentioning
confidence: 99%
“…At low temperature, that is, between 423 and 523 K, the oxidation step involves transient dimeric [Cu­(NH 3 ) 2 –OO–Cu­(NH 3 ) 2 ] 2+ species whose formation requires the simultaneous presence of two [Cu­(NH 3 ) 2 ] + monomers in the same cha cage. The hops between adjacent cha cages are modulated by size exclusion effects and also by the attractive interaction between the positively charged [Cu­(NH 3 ) 2 ] + complexes and the negatively charged framework Al sites. ,,,, Thus, structural properties such as the Al content and distribution, Cu loading, and Brønsted acid site density as well as the interaction of the Cu active sites with the reactants, in particular, NH 3 , might affect the mobility of Cu cations and consequently the NH 3 –SCR–NO x reaction rate. This has been evidenced by recent studies combining catalytic activity tests with operando XAS or EPR spectroscopy, and ab initio molecular dynamics (AIMD) simulations have been successfully applied to provide atomistic insight into the dynamic nature of the Cu + cations under reaction conditions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Assessing the structure, formation pathways, and reactivity of mono-or multimeric Cuoxo fragments presents a challenging platform for chemical scientists. Translating knowledge of Cu ion mobility and redox properties into the area of the direct conversion of methane to methanol may be important to better understand the redox properties of the transition metal ions in zeolites and to improve catalyst design and catalytic processes [63].…”
Section: Znmor-ac Cuomentioning
confidence: 99%
“…However, Cu(I) ions can be located in the vicinity of a single Al atom (not present in the Al-rich matrix of Y-zeolite); moreover, they can be mobile and thus do not represent a suitable probe for binuclear TMI sites active in methane oxidation. 13 Our recent study showed that divalent Zn ions located in extra-framework positions of the ferrierite matrix (accommodated by Al pairs) exhibit similar luminescence properties as Cu(I) ions in zeolites and Zn(II) emission wavelength can be employed for the identification of Zn(II) siting. 14 Therefore, the quenching of Zn(II) luminescence by other divalent cations of transition metal ions (M(II)) can be suggested as a possible way to prove the presence of two M(II) ions in close vicinity forming binuclear TMI sites.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a possible way to verify the presence of binuclear sites is performing the reaction testsplitting of molecular oxygen and subsequent reaction with methane. , However, it is already reported that the luminescence of Cu­(I) ions located in extra-framework cation sites of zeolite Y can be quenched by other TMI ions (Ni, Co, or Mn) when located close enough, which opens the possibility to develop a method for the analysis of the presence of two cations at a close distance. However, Cu­(I) ions can be located in the vicinity of a single Al atom (not present in the Al-rich matrix of Y-zeolite); moreover, they can be mobile and thus do not represent a suitable probe for binuclear TMI sites active in methane oxidation . Our recent study showed that divalent Zn ions located in extra-framework positions of the ferrierite matrix (accommodated by Al pairs) exhibit similar luminescence properties as Cu­(I) ions in zeolites and Zn­(II) emission wavelength can be employed for the identification of Zn­(II) siting .…”
Section: Introductionmentioning
confidence: 99%